(untitled) (Brazilian Journal of Oceanography, 2014)
The Mid Atlantic Ridge (MAR) is a seamount chain extending for 60.000 km, divided into south and north regions by the Equatorial Fracture which cuts across it. This latter has a maximum depth of 7,760 m and an average width of 19 km. In this study we include data from the two cruises of the international project MAR-ECO, undertaken, respectively, one on the north and the other on the south MAR. Our main objective is to compare the species richness and species composition of pelagic and benthic decapod shrimps of these two areas to observe the patterns of their latitudinal distribution along the MAR. Using rarefaction methods, we obtained interesting results: the pelagic samples curve of the northern MAR is almost an asymptote, so we concluded that we are close to the true number of pelagic shrimp species for this region. The pelagic samples curve of the southern MAR had the greatest slope, so our conclusion is that we are still far from the true number of species for this region. A comparison of species richness at 12 samples (the smallest number of samples shared by both the surveys) revealed that the pelagic species richness was greater than the demersal, and that the northern MAR contained a larger number of species than the southern.